Assessment of Quality of Pain and Patient Satisfaction using ASSIST Questionnaire Following Intraperitoneal Instillation of Ropivacaine Compared with the Addition of Adjuncts Ketamine versus Dexmedetomidine in Laparoscopic Cholecystectomy patients - Kapoor, Ruchi; Dua, Steffi; Saxena, Ashok Kumar (Journal of Anaesthesia and Pain, 2024)
Background: Evaluation of patient satisfaction score and to assess quality of pain relief following intraperitoneal instillation of Ropivacaine with adjuncts Dexmedetomidine vs Ketamine using modified version of revised APS-POQ in patients undergoing laparoscopic cholecystectomy.Methods: Sixty patients undergoing laparoscopic cholecystectomy were randomised into three groups of  20 each and received Ropivacaine 0.2 % (group R), Ropivacaine 0.2 % with Dexmedetomidine 0.7µg/ kg (group RD) and Ropivacaine with Ketamine 0.5 mg/kg (group RK) in a total volume of 40 ml. Pain severity, subjective pain complaints, pain interference in physical activity, and patient's and caregiver's satisfaction were evaluated using a modified version of the revised APS-POQ at 24 hours postoperatively.Result: Mean pain scores for worst pain were observed to be least in Group RD, with mean values being 1.75±1.743, followed by 5.45±1.701 in Group R and mean value of 5.60±0.754 in Group RK. Mean patient satisfaction scores were found to be highest in Group RD (94.00±8.826), followed by Group R (80.00±15.218), and least in Group RK (78.50±12.258). This difference was observed to be statistically significant (p<0.05) in all groups. Primary care physicians caring for the RD group had higher satisfaction scores (9.40±0.883) compared to Group RK (7.85±1.226) and Group R (8.05±1.468)Conclusion: Quality of pain relief improved the best with Dexmedetomidine followed by Ketamine and least when Ropivacaine used alone for intraperitoneal instillation. The overall patients' satisfaction was found to be more with Ropivacaine with Dexmedetomidine when compared to Ropivacaine alone or with Ketamine